Effect of sucrose concentration on producction of anthocyanins from cell cultures of Vitis vinifera L. var. red globe - Miñano, Antonieta (2004)
Vitis vinifera «grape» is one edible fruit vine of importance in agriculture activities, besides to have medical properties related to bioactive natural products knowing as anthocyanins, that, they exhibit antioxidative, anticancerigen and cardiotonic activities. In this paper, a system of suspension cell cultures from Vitis vinifera «vid» var. red globe was established to determine the effect of the concentration of sucrose on anthocyanins yield. Different concentrations of sucrose (0 mM, 58 mM, 132 mM and 175 mM) into Basal culture Media (BM) supplemented with separated concentrations of naftalnacetic acid and kinetine as Inductor Media (IM), were applied. Anthocyanins yield were increased in according to increment of sucrose concentration (132mM) in the cell culture. Significant differences among the treatments were founded.